Asian Americans' concerns and plans about Alzheimer's disease: The role of exposure, literacy and cultural beliefs. (4th October 2017) - Jang, Yuri; Yoon, Hyunwoo; Park, Nan Sook; Rhee, Min‐Kyoung; Chiriboga, David A.
Abstract: Responding to the increase of the Asian American population and the growing imperative to address issues on Alzheimer's disease (AD) in diverse populations, this study examined Asian Americans' concerns about AD (both concerns about one's own development of AD and about becoming an AD caregiver) and plans for AD. Focus was given on exploring the role of AD exposure, AD literacy and cultural beliefs about AD in predicting AD‐related concerns and plans. Using data from 2, 609 participants in the 2015 Asian American Quality of Life survey (aged 18–98), logistic regression models of three outcome measures (concerns about one's own development of AD, concerns about becoming an AD caregiver and plans about AD) were estimated. AD exposure and literacy (perceived knowledge and awareness of services) were common predictors of all three outcomes. Beliefs that associate AD with a normal part of ageing and a matter of fate increased the odds of having AD concerns. The odds of having AD plans were found to be higher among those with such concerns. Findings not only identified the factors associated with the concerns and plans about AD but also informed ways to develop targeted AD interventions for Asian Americans.